High-CBD Extract (CBD-X) Downregulates Cytokine Storm Systemically and Locally in Inflamed Lungs - Aswad, Miran; Hamza, Haya; Pechkovsky, Antonina; Zikrach, Anastasiia; Popov, Tania; Zohar, Yaniv; Shahar, Eduardo; Louria-Hayon, Igal (Frontiers in Immunology, 2022)
Cytokine storm refers to the dysregulated production of inflammatory mediators leading to hyperinflammation. They are often detrimental, and worsen the severity of COVID-19 and other infectious or inflammatory diseases. Cannabinoids are known to have anti-inflammatory effects but their possible therapeutic value on cytokine storms has not been fully elucidated. In vivo and ex vivo studies were carried out to investigate the effects of high-THC and high-CBD extracts on cytokine production in immune cells. Significant differences between the extracts were observed. Subsequent experiments focusing on a specific high CBD extract (CBD-X) showed significant reductions in pro-inflammatory cytokines in human-derived PBMCs, neutrophils and T cells. In vivo mouse studies, using a systemically inflamed mouse model, showed reductions in pro-inflammatory cytokines TNFα and IL-1β and a concurrent increase in the anti-inflammatory cytokine IL-10 in response to CBD-X extract treatment. Lung inflammation, as in severe COVID-19 disease, is characterized by increased T-cell homing to the lungs. Our investigation revealed that CBD-X extract impaired T-cell migration induced by the chemoattractant SDF1. In addition, the phosphorylation levels of T cell receptor (TCR) signaling proteins Lck and Zap70 were significantly reduced, demonstrating an inhibitory effect on the early events downstream to TCR activation. In a lung inflamed mouse model, we observed a reduction in leukocytes including neutrophil migration to the lungs and decreased levels of IL-1β, MCP-1, IL-6 and TNFα, in response to the administration of the high-CBD extract. The results presented in this work offer that certain high-CBD extract has a high potential in the management of pathological conditions, in which the secretion of cytokines is dysregulated, as it is in severe COVID-19 disease or other infectious or inflammatory diseases.